Improved dielectric properties of La2O3–ZrO2 bilayer films for novel gate dielectrics. (August 2020) - Li, Shuan; Lin, Youyu; Li, Guoling; Yu, Hongen; Tang, Siyao; Wu, Yiman; Li, Xingguo; Tian, Wenhuai
Abstract: La2 O3 film with large theoretical k value and ZrO2 film with large theoretical band gap are selected to fabricate bilayer composite dielectric films by magnetron sputtering. La2 O3 –ZrO2 bilayer films combine the advantages of both La2 O3 and ZrO2 films. We demonstrate that Pt/La2 O3 –ZrO2 /Si MOS capacitor is more favorable for transistors than Pt/ZrO2 –La2 O3 /Si MOS capacitor, featuring for a larger dielectric constant (12.37) and a lower leakage current (3.5 × 10 −4 A/cm 2 ). Besides, our results indicate that optimal sublayer thicknesses of La2 O3 and ZrO2 film are both 10 nm as well as the optimal temperature is 500 °C, which represents a significantly improved performance of larger dielectric constant (13.34) and lower leakage current density (8.19 × 10 −5 A/cm 2 ). Highlights: La2 O3 –ZrO2 /Si stack as a novel gate dielectric is prepared by sputtering. La2 O3 –ZrO2 bilayer films combine the advantages of both La2 O3 and ZrO2 films. Sublayer thicknesses and annealing temperature of La2 O3 –ZrO2 bilayer films were optimized. The leakage current transport mechanisms have been discussed in detail.